Animal models of pediatric chronic kidney disease. Is adenine intake an appropriate model? - Débora Claramunt (Nefrología, 2015)
Pediatric chronic kidney disease (CKD) has peculiar features. In particular, growth impairment is a major clinical manifestation of CKD that debuts in pediatric age because it presents in a large proportion of infants and children with CKD and has a profound impact on the self-esteem and social integration of the stunted patients. Several factors associated with CKD may lead to growth retardation by interfering with the normal physiology of growth plate, the organ where longitudinal growth rate takes place. The study of growth plate is hardly possible in humans and justifies the use of animal models. Young rats made uremic by 5/6 nephrectomy have been widely used as a model to investigate growth retardation in CKD. This article examines the characteristics of this model and analyzes the utilization of CKD induced by high adenine diet as an alternative research protocol.